Ciclo Reprodutivo de Perna Perna (linnaeus, 1758): um Biomarcador para Áreas Antrópicas? - Franca, Millena Araujo (2020)
Coastal populations use the oceans for communication, transportation, recreation or food sources, however, these food sources over the past centuries have suffered and routinely suffer from the impacts of anthropic action. Among the targ